On some characterizations of classical operators of composition Hardy type - Anupama Gupta (International Journal of Advanced Mathematical Sciences, 2024)
In this paper, we study classical operators of composite Hardy type on Lp− space. Our focus is to discuss some operator theoretic properties of the classical operators of composite Hardy type. An attempt has been made to compute the nth approximation number of classical operators of composite Hardy type. Keywords: Classical operators of Composite Hardy type; Composition operator; Expectation operator; Radon- Nikodym derivative.